2015
DOI: 10.1002/maco.201408203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tartrate on the electrochemical behaviour and semiconductive properties of passive film on steel in saturated calcium hydroxide

Abstract: This paper presents results of the basic study on the inhibitive action of tartrate toward chloride‐induced corrosion on carbon steel rebar in alkaline environment. Modification of the electrochemical behaviour and semiconductive properties of passive film formed on steel surface in the presence of tartrate were characterised by a range of electrochemical techniques in saturated calcium hydroxide. In the presence of tartrate in saturated calcium hydroxide with addition of 0.14 M sodium chloride pitting corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The need to reach more negative potentials to initiate the deposition can suggest a surface inhibition effect, stronger when compared with lactate, caused by the adsorption of tartrate and/or its complexes. This evidence agrees with lower cathodic currents (at higher potentials in the positive sweep and lower potentials in the negative sweep) depicted in Figure a and the surface protective effect of the tartrate molecules found in the corrosion science literature. For a detailed investigation of the pH effect on the CV and the galvanodynamic curves, please see Figures S1 and S2 in the Supporting Information, respectively.…”
Section: Resultssupporting
confidence: 85%
“…The need to reach more negative potentials to initiate the deposition can suggest a surface inhibition effect, stronger when compared with lactate, caused by the adsorption of tartrate and/or its complexes. This evidence agrees with lower cathodic currents (at higher potentials in the positive sweep and lower potentials in the negative sweep) depicted in Figure a and the surface protective effect of the tartrate molecules found in the corrosion science literature. For a detailed investigation of the pH effect on the CV and the galvanodynamic curves, please see Figures S1 and S2 in the Supporting Information, respectively.…”
Section: Resultssupporting
confidence: 85%
“…At the same time, the presence of the negative carboxylate group of the tartrate on the film surface counteracts the adsorption of the chloride ions, favoring the re-passivation. The same authors also reported that increasing the concentration of tartrate above 2.5 × 10 −3 M results in the deterioration of passive film due to the dissolution of the surface complex induced by the lowering metal/ligand ratio [42]. For this reason, the overall effect of tartrate ions on carbon steel could be to enhance the generalized dissolution of the passive film, but, at the same time, its carboxylate groups counteract the adsorption of the chlorides on the film surface, inhibiting the localized corrosion onset and propagation.…”
Section: Resultsmentioning
confidence: 85%
“…The competitive formation of soluble complexes of Fe (III) and the adsorption of the tartrate ions on the electrode surface to substitute the hydroxyl in the passive film, increases the current density in the passive range of potential, but, at the same time, inhibits the adsorption of chloride ions, and, as a consequence, the pitting initiation. In the inhibition mechanism proposed by Valek Žulj et al, the tartaric acid stabilized the Fe (III) in the passive film; as a consequence of this, the concentration of Fe (II) ions in the film decreases, and, in this way, the conductivity of the n-type semiconductor passive film is reduced, for the decreasing of the concentration of the donors, reducing the efficiency of the occluded cell in the propagation of the localized attack [42]. At the same time, the presence of the negative carboxylate group of the tartrate on the film surface counteracts the adsorption of the chloride ions, favoring the re-passivation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations